Transitioning Out of the Coronavirus Lockdown: A Framework for Evaluating Zone-Based Social Distancing - Friedman, Eric; Friedman, John; Johnson, Simon; Landsberg, Adam (Frontiers in Public Health, 2020)
In the face of elevated pandemic risk, canonical epidemiological models imply the need for extreme social distancing over a prolonged period. Alternatively, people could be organized into zones, with more interactions inside their zone than across zones. Zones can deliver significantly lower infection rates, with less social distancing, particularly if combined with simple quarantine rules and contact tracing. This paper provides a framework for understanding and evaluating the implications of zones, quarantines, and other complementary policies.